Nutritive value of palm oil sludge fermentation by some incubation process - I.A.B, Bintang; Sinurat, A.P; Purwadaria, T; Pasaribu, T (Indonesian Journal of Animal and Veterinary Sciences, 2000)
An experiment was conducted to study the effect of fermented palm oil sludge (PaS) incubated with different ways towards metabolic digestibility on dry matter,true metabolizable energy (TME) and protein digestibilities. A completely randomized design was used. Treatments consisted of unfermented pas (control) and fermented pas with and without enzymatic incubation proces, two levels of incubation temperatures (28°C and 32°C) and three levels of incubation times (3, 4 and 5 days). The digestibility studies were carried out in 46 layer. The results showed that the dry matter digestibility of P_S was not significantly affected by fermentation process neither by incubation times. TME was not affected by fermentation process and incubation times, but it was significantly affected by incubation temperatures during fennentation (P<0,05). Incubation temperatures at 3rC more significant than 28°C. Enzimatic process was more significant than without enzimatic process. True metabolizable energy was highly significantly affected by enzimatic process (P<O,OI). Protein digestibility was highly significantly affected by time and incubation process (P<O,Ol), but not significantly affected by temperatures incubation. It was concluded that fermentation process could improve the digestibility of palm oil sludge (paS). The best result obtained from incubation at 32°C for 3 days and continued by enzimatic process.   Key words: Fennentation, nutritive value, palm oil sludge